(3.5x-3)=6x-10

Simple and best practice solution for (3.5x-3)=6x-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3.5x-3)=6x-10 equation:



(3.5x-3)=6x-10
We move all terms to the left:
(3.5x-3)-(6x-10)=0
We get rid of parentheses
3.5x-6x-3+10=0
We add all the numbers together, and all the variables
-2.5x+7=0
We move all terms containing x to the left, all other terms to the right
-2.5x=-7
x=-7/-2.5
x=2+1/1.25

See similar equations:

| -812=-28(k-962) | | 21/20=35/x | | 39=11+7x | | x+5=11+x-7 | | 7x-11=-19-F3x | | 11+(x)-7=(x)+5 | | 4y+(-20)=-60 | | 7=6(e+5)/11 | | 7x-11=—19-F3x | | -15+h=-25 | | 37=2-5v | | 35/21=20/x | | -2g+-281=281 | | 8=-2+u/2 | | 0.3a=-3= | | X+4=3x-8x= | | 8(x-9)=2 | | 8(g+-17)=-40 | | -14x-96=192-2x | | -6x-67=25-2x | | -152=8x-7(8-8x) | | 20/21=35/x | | -15+8k=25 | | 4=s/7-3 | | 3.1/4=1/2z | | 3x-5/56=5x-5/32 | | r+678=858 | | 10=|-15+3c | | 1/2(4x-2)=2(x+4)-9 | | 40=8(r+32) | | ⅖+m=⅚ | | 4=s7− 3 |

Equations solver categories